Optimization of Hemoglobin Encapsulation within PLGA Nanoparticles and Their Investigation as Potential Oxygen Carriers - Clara Coll-Satue; Michelle Maria Theresia Jansman; Peter Waaben Thulstrup; Leticia Hosta-Rigau (MDPI AG, 2021)
Hemoglobin (Hb)-based oxygen carriers (HBOCs) display the excellent oxygen-carrying properties of red blood cells, while overcoming some of the limitations of donor blood. Various encapsulation platforms have been explored to prepare HBOCs which aim to avoid or minimize the adverse effects caused by the administration of free Hb. Herein, we entrapped Hb within a poly(lactide-co-glycolide) (PLGA) core, prepared by the double emulsion solvent evaporation method. We study the effect of the concentrations of Hb, PLGA, and emulsifier on the size, polydispersity (PDI), loading capacity (LC), and entrapment efficiency (EE) of the resulting Hb-loaded PLGA nanoparticles (HbNPs). Next, the ability of the HbNPs to reversibly bind and release oxygen was thoroughly evaluated. When needed, trehalose, a well-known protein stabilizer that has never been explored for the fabrication of HBOCs, was incorporated to preserve Hb's functionality. The optimized formulation had a size of 344 nm, a PDI of 0.172, a LC of 26.9%, and an EE of 40.7%. The HbNPs were imaged by microscopy and were further characterized by FTIR and CD spectroscopy to assess their chemical composition and structure. Finally, the ability of the encapsulated Hb to bind and release oxygen over several rounds was demonstrated, showing the preservation of its functionality.